1994
DOI: 10.1007/bf01534440
|View full text |Cite
|
Sign up to set email alerts
|

Migratory activity of blood polymorphnuclear leukocytes during juvenile rheumatoid arthritis, demonstrated with a new wholeblood membrane filter assay

Abstract: Polymorphonuclear leukocyte (PMN) migration is measured in whole blood in a migration chamber consisting of a membrane filter (3-microns pores, 140 microns thick) with an integrated chemoattractant depot (FMLP in solid form) attached to a plastic container. Control chambers lack FMLP (blanks). One test unit requires 300 microliters blood. Numbers and distribution of the PMN immigrants into the filters are determined microscopically. Altogether 26 measurements of PMN migration in five juvenile rheumatoid arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Data on neutrophil function in JRA are hard to find (37,38), but there is evidence that neutrophils represent an important cellular component that contributes to synovial inflammation (39)(40)(41). Previous studies demonstrated the influence of TNF␣ on neutrophil infiltration in arthritis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Data on neutrophil function in JRA are hard to find (37,38), but there is evidence that neutrophils represent an important cellular component that contributes to synovial inflammation (39)(40)(41). Previous studies demonstrated the influence of TNF␣ on neutrophil infiltration in arthritis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in good agreement with earlier studies by our working group on other topics demonstrating that the mere number of circulating PMNs does not necessarily reflect their immunological efficiency, and functional parameters are much more reliable. Before infections, we often found a low PMN readiness to migrate that coincided with elevated blood counts feigning an effective host defense [11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…With increasing duration and degree of impaired PMN migration, the risk of infection increased in parallel, eventually resulting in the clinical manifestation of an infection. In this way, it was possible to predict impending infections [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…They express the reactivity of a PMN collective to FMLP in comparison with the unstimulated, spontaneous migration. For more details about the method see [8].…”
Section: Pmn Functional Parametersmentioning
confidence: 99%